Reference curves for CD4 T‐cell count response to combination antiretroviral therapy in HIV‐1‐infected treatment‐naïve patients. Issue 1 (14th September 2016) - Bouteloup, V; Sabin, C; Mocroft, A; Gras, L; Pantazis, N; Le Moing, V; d'Arminio Monforte, A; Mary‐Krause, M; Roca, B; Miro, JM; Battegay, M; Brockmeyer, N; et al.
Abstract : Objectives: The aim of this work was to provide a reference for the CD4 T‐cell count response in the early months after the initiation of combination antiretroviral therapy (cART) in HIV‐1‐infected patients. Methods: All patients in the Collaboration of Observational HIV Epidemiological Research Europe (COHERE) cohort who were aged ≥ 18 years and started cART for the first time between 1 January 2005 and 1 January 2010 and who had at least one available measurement of CD4 count and a viral load ≤ 50 HIV‐1 RNA copies/mL at 6 months (± 3 months) after cART initiation were included in the study. Unadjusted and adjusted references curves and predictions were obtained using quantile regressions. Results: A total of 28 992 patients were included in the study. The median CD4 T‐cell count at treatment initiation was 249 [interquartile range (IQR) 150, 336] cells/ μ L. The median observed CD4 counts at 6, 9 and 12 months were 382 (IQR 256, 515), 402 (IQR 274, 543) and 420 (IQR 293, 565) cells/ μ L. The two main factors explaining the variation of CD4 count at 6 months were AIDS stage and CD4 count at cART initiation. A CD4 count increase of ≥ 100 cells/mL is generally required in order that patients stay 'on track' (i.e. with a CD4 count at the same percentile as when they started), with slightly higher gains required for those starting with CD4 counts in the higher percentiles. Individual predictions adjusted for factors influencing CD4 count were more precise. Conclusions: Reference curves aid the evaluation of the immune response early after antiretroviral therapy initiation that leads to viral control.